Evaluating the performance of Malaysia Hematite and its mixtures with barite as weighting material in water-based mud - Ismail, Issham; Abdul Kadir, Abdul Aziz (Faculty of Chemical & Natural Resources Engineering, UTM Skudai, 1997)
This paper discusses the prospect of using Malaysia hematite as weighting material in water-based mud. The discussion is based on laboratory experiments. Currently, in the petroleum industry, barite (commercial name for barium sulphate) is the standard weighting material used to elevate mud weight to a predetermined value. The supply of quality barite may fall short in the foreseeable future due to the increase in drilling activities and depleting reserves of quality barite. Thus there is a need to look for and alternative weighting material. In this study, the performance of Malaysia hematite and it’s mixtures with barite were compared to barite, the standard weighting material used in the petroleum industry, in water-based mud. The experimental results revealed that for a given mud density, mud sample with higher percentage of hematite produced higher yield point and gel strength. Nevertheless, it produced little differences in plastic viscosity. The significant advantage realized in utilizing hematite was it gave a lower solid content. The experimental study also revealed that hematite was found to be more abrasive than barite. The abrasiveness rate was found increase proportionally with the well angles (from horizontal). Based on this preliminary study, it is concluded that Malaysia hematite has the potential to be used as weighting material in drilling mud.